Unitary model for the analysis of bolted connections using the finite element method - Vilela, Paula Moura Leite; Carvalho, Hermes; Grilo, Lucas Figueiredo; Montenegro, Pedro Aires; Calçada, Rui Bártolo (Engineering failure analysis, 2019)
This paper presents the numerical simulation of a model with one bolt connecting two or three plates using the finite element method. This unitary model with one bolt is validated by comparing its results with those obtained in the literature for three different types of applied load: tension, shear, and a combination of both. The results are also compared with the American and Brazilian design codes. The unitary model includes all necessary considerations: contacts between the plates and the nut, head and shank of the bolt; contact between the plates, as well as the friction between them; and pre-load on the bolt. Moreover, it responds properly to forces parallel and perpendicular to the contact surface between the plates including prying action effects and slip. These calibrated models can be then introduced on a model that represents a full connection through a relatively simple process using ANSYS APDL language, thus allowing the study of any bolted connection type. •Development of a unitary numerical model for simulation of the bolted connections, considering contact and pre-load on the bolt;•Validation of numerical models through experimental results for three different types of applied load: tension, shear, and a combination of both.•Comparison of the numerical results obtained with the American and Brazilian design codes.